ATP-Nlrp3 Inflammasome-Complement Cascade Axis in Sterile Brain Inflammation in Psychiatric Patients and its Impact on Stem Cell Trafficking - Ratajczak, Mariusz Z. (Stem Cell Rev, 2019)
Recent evidence indicates that the occurrence of psychiatric disorders in patients is linked to a local “sterile” inflammation of brain or due to a systemic inflammation process that affects the central nervous system. This is supported by the observation that in peripheral blood of psychotic patients are detectable several mediators and markers of inflammation as well as clinical data on correlations between systemic chronic inflammatory processes and psychiatric disorders. This may explain why some reported anti-inflammatory treatment strategies have beneficial effects on ameliorating psychotic events. In this review we will present a concept that aberrant purinergic signaling and increases in extracellular level of adenosine triphosphate (ATP) in the brain parenchyma may lead to activation of Nlrp3 inflammasome in microglia cells and as a consequence microglia released danger associated molecular pattern (DAMP) proteins activate complement cascade (ComC) in mannan binding lectin (MBL) – dependent manner. Activation of ATP-Nlrp3 inflammasome-ComC axis may also orchestrate trafficking of stem cells released from bone marrow into peripheral blood observed in psychotic patients. Based on this, the ATP-Nlrp3 inflammasome-ComC axis may become a target for new therapeutic approaches, which justifies the development and clinical application of efficient anti-inflammatory treatment strategies targeting this axis in psychiatry.